2022
DOI: 10.56373/2022-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Tannhelsetjenester i norske fengsler

Abstract: Hovedbudskap Akutt behandling opptar mesteparten av arbeidsbyrden for tannleger i fengsler Tannbehandlingsangst er et stort hinder for undersøkelse og behandling Det utføres lite tannhelsefremmende og forebyggende arbeid i fengsler Innsatte er en gruppe som bør ses nærmere på i forbindelse med den kommende offentlige utredningen om tannhelsetjenester

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Assuring good oral health for people living in prisons is described as an international challenge. It is often related to the lack of staffing and logistical issues during transfer to and from dental clinics [3,5,6]. These barriers may also explain why, in Norwegian prisons, emergency dental treatment tends to be the most sought reason for dental care [6].…”
Section: Original Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuring good oral health for people living in prisons is described as an international challenge. It is often related to the lack of staffing and logistical issues during transfer to and from dental clinics [3,5,6]. These barriers may also explain why, in Norwegian prisons, emergency dental treatment tends to be the most sought reason for dental care [6].…”
Section: Original Manuscriptmentioning
confidence: 99%
“…Promoting and assuring good oral health for people in prisons has been advocated at structural levels by The World Health Organization's Prison Programmes, calling for health promotion to be equal outside as within prisons [11], and at the dental practitioners level [6]. Assuring and promoting good oral health is different globally.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…Dental health services are provided either in a prison dental clinic or outside the prison detention centre [19]. However, recent findings from a Norwegian study indicated that dental appointments were made primarily for urgent emergency treatment and that the public dental health service had a low focus on preventing illness and promoting oral health in prisons [19]. A pilot study in a Norwegian prison found that prisoners had poor knowledge of the relationship among diet, oral hygiene, and oral health [20].…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, prisoners have the right to free emergency dental treatment when admitted to prison, as well as free examinations and treatment required for sustaining acceptable oral health if sentenced to more than three months [17, 18]. Dental health services are provided either in a prison dental clinic or outside the prison detention centre [19]. However, recent findings from a Norwegian study indicated that dental appointments were made primarily for urgent emergency treatment and that the public dental health service had a low focus on preventing illness and promoting oral health in prisons [19].…”
Section: Introductionmentioning
confidence: 99%